The Paradox of Political Participation: Theorizing Uncivil Society - Eder, Klaus (PARTECIPAZIONE E CONFLITTO, 2014)
The paper addresses the phenomenon of civil societies turning into uncivil societies and the capacity of civil societies for self-repair. Confronted with the recent events of the rise and fall of civil society in the “Arab Spring” and in the Ukrainian Maidan movement a conceptual framework is offered for accounting for such rise and fall. It starts with the paradox that participation in public debate equally produces civil and uncivil outcomes, thus taking up the classic thesis of the “fall of reason” formulated in the tradition of “critical theory” on the “dialectics of enlightenment”. Such “dialectics” results from the interplay of three mechanisms that shape the making of a civil society: the rule of law, the market and the forum. These mechanisms have their specific historical legacy in political and social philosophy. Civil society praised by some as the outcome of the rule of law, by others as the outcome of free markets and by others as the outcome of free speech, empirically does not stand up to these normative expectations. These mechanisms produce “perverse effects”, grasped by the metaphor of monsters representing the rule of law and the market: Leviathan (the perverse effects of the rule of law) and Behemoth (the perverse of the market). These perverse effects cumulate in the emergence of uncivil society as the apotheosis of unreason. Fascism is a case for the perverse effects of public communication and political mobilization of people. After identifying the third monster, I will put forward the argument that the forum works not only as mechanism of repairing the rule of law and the market, but also as a “mechanism of self-repair” of civil society